Brown Rabbit's shape book - Baker, Alan, 1951- (New York : Kingfisher Books, 1999)
Brown Rabbit finds a box of balloons and creates various shapes from them.
3 13 17 21
Keywords: Balloons -- Juvenile fiction; Rabbits -- Juvenile fiction; Form perception -- Juvenile fiction